Equilibrium Study and Biological Activity of Cu(II) with Polyvinyl alcohol(PVA) and Some Amino acids and DNA - Hosny, Wafaa; Khalaf- Alaa, Perihan (JOURNAL OF ADVANCES IN CHEMISTRY, 2007)
This study presents the acid-base equilibrium of polyvinyl alcohol (PVA). The stability constant values of the binary and ternary complexes formed in solution among polyvinyl alcohol, Cu (II), some amino acids and DNA were determined potentiomertically. The stability constants of the complexes are determined and the concentration distribution diagrams of the complexes are evaluated. The ligand and their metal chelates have been screened for their antimicrobial activities using the disc diffusion method against the selected bacteria and fungi. Binary and ternary complexes of copper (II) involving polyvinyl alcohol (PVA) and various biologically relevant ligands containing different functional groups, were investigated. The ligands (L) are amino acids and DNA constituents. The ternary complexes of amino acids and DNA are formed by simultaneous reactions respectively. The results showed the formation of Cu (PVA) (L) complexes with amino acids and DNA. Amino acids form both Cu (PVA)(L) complexes and the corresponding protonatedÂ Cu(PVA)(LH) and deprotonated species Cu(PVA)(LHâˆ’1). The ternary complexes of copper (II) with (PVA) and DNA are formed in a stepwise process, whereby binding of copper (II) to (PVA) is followed by ligation of the DNA components. DNA constituents form 1:1 complexes with Cu (PVA). The stability of these ternary complexes was quantitatively compared with their corresponding binary complexes in terms of the parameter âˆ† log10K. The values of âˆ† log10K indicate that the ternary complexes containing aromatic amino acids were significantly more stable than the complexes containing alkyl- and hydroxyl alkyl substituted amino acids. The concentration distribution of various complex species formed in solution was also evaluated as a function of pH. The antimicrobial activities using the disc diffusion method against some selected bacteria and fungi. The activity data show that the metal complexes are found to have antibacterial and antifungal activity.